PENGARUH NET INTEREST MARGIN (NIM), NON PERFORMING LOAN (NPL) DAN BOPO (BIAYA OPERASIONAL PADA PENDAPATAN OPERASIONAL) TERHADAP RETURN ON EQUITY (ROE) PADA BANK UMUM NASIONAL YANG TERDAFTAR DI BEI - Didin Rasyidin Wahyu; Iis Nurasiah; Rizki Nebula Triananda Putri (LP2M Universitas Bina Bangsa, 2023)
The purpose of this study was to determine whether NIM, NPL and BOPO affect ROE at National Commercial Banks listed on the Indonesia Stock Exchange for the period 2015-2019. This research method uses quantitative research methods, the population of all National Commercial Banks listed on the IDX for the 2015-2019 period and a sample of 6 companies based on the purposive sampling method, data collection techniques use secondary data, the data analysis technique used in this study consists of statistical descriptions, classical assumption test, multiple linear regression analysis and coefficient of determination, statistical hypotheses consist of partial analysis (T-test) and simultaneous analysis (F-test). Based on the results of research and statistical calculations, it is known that the t-test (partial) obtained the NIM t-count value of -0.166> t_ (table) -2.048, the NPL t-count value of -2.840 <-t_ (table) -2.048, the BOPO t count value of -0.372 < t_ (table) -2.048 and the results of the f-test (simultaneous) obtained the F_count value of 4,972> F_ (table) 2.98. Thus it can be concluded that partially NIM does not have a negative effect on ROE, NPL has a negative effect on ROE, while OEOI has no negative effect on ROE and simultaneously NIM, NPL and BOPO have an effect on ROE at National Commercial Banks listed on the Stock Exchange. Indonesia for the period 2015-2019.